2023
DOI: 10.1186/s12915-023-01793-x
|View full text |Cite
|
Sign up to set email alerts
|

Animal welfare research is fascinating, ethical, and useful—but how can it be more rigorous?

Georgia J. Mason

Abstract: The scientific study of animal welfare supports evidence-based good animal care, its research contributing to guidelines and policies, helping to solve practical problems caused by animal stress, and raising fascinating questions about animal sentience and affective states. However, as for many branches of science (e.g. all those with replicability problems), the research rigour of welfare science could be improved. So, hoping to inspire methodologies with greater internal, external, and construct validity, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Studies focusing on laboratory animals were abundant, showing that the concern to improve the welfare of these animals is great since they are often used in biomedical research and the results of such research need to be reliable [ 41 , 42 , 43 ]. Some studies have already shown that low levels of welfare in these animals can generate dubious results in these studies [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies focusing on laboratory animals were abundant, showing that the concern to improve the welfare of these animals is great since they are often used in biomedical research and the results of such research need to be reliable [ 41 , 42 , 43 ]. Some studies have already shown that low levels of welfare in these animals can generate dubious results in these studies [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%